Synthesis and Characterization of Some Heterocyclic Compounds and Evaluation of their Antioxidant Activity - Auhood Kadhim Zaid (Journal of Global Pharma Technology, 2019)
This study is concerned with the synthesis and characterization of five derivatives of two groups of heterocyclic compounds, dihydroprimidine (DHPM) and imidazole. The DHPM derivatives were [benzyl 6-methyl-4-(naphthalen-2-yl)-2-thioxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (1a)], [benzyl 6-methyl-4-(naphthalen-2-yl)-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (2a)] and [benzyl 4-(1-hydroxynaphthalen-2-yl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (3a)] and the imidazole compounds were [1,4-bis(4-(4-bromophenyl)-1-(3-chlorophenyl)-1H-imidazol-2-yl) benzene (1b)] and [1,4-bis(4-(4-bromophenyl)-1-phenyl-1H-imidazol-2-yl)benzene (2b)]. Biological testing revealed the prepared compounds to have antioxidant properties. Keywords: Antioxidants, Heterocyclic compounds, Dihydroprimidine, Imidazole, Biological activity.